Analisis Pengaruh Penerapan Sistem Manajemen Enterprise Resource Planning (Erp) Dalam Meningkatkan Supply Chain Management (Scm) Pada Perusahaan Indofood Tbk - Eva Awaliya, Nindi Suhendri, Tiara Plorist Sibarani Lilian Nurul Wildani,; Feby Safa Zabrina, Wisnu Yuwono , Fitriana Aidnilla Sinambela (Jurnal Mirai Management, 2023)
This article discusses the influence of implementing the Enterprise Resource Planning (ERP) management system in improving Supply Chain Management (SCM) at PT Indofood Tbk. This study aims to evaluate the implementation of ERP at PT Indofood Tbk, with a focus on its impact on SCM effectiveness. The research method used is a descriptive qualitative analysis technique related to SCM and the company's ERP system. The final results show that the implementation of the ERP system at PT Indofood Tbk has contributed positively to the company's SCM effectiveness. In this case, the ERP system helps improve overall supply chain management efficiency and effectiveness. This efficiency improvement includes reducing delivery cycle times and costs, as well as increasing the accuracy of inventory management. Thus, the implementation of the ERP system has had a positive impact on SCM effectiveness at PT Indofood Tbk, and serves as a successful example for other companies to improve their supply chain management efficiency and effectiveness. Keywords: Enterprise Resource Planning (ERP), Supply Chain Management (SCM), PT Indofood Tbk.